Training farmer groups on developing business plans, accessing markets, financial management and creating databases for trade - Le, Pham Thi; Thinh, Nguyen-Thi; Thanh, Lo Quang (International Livestock Research Institute, 2024)
SAPLING is one of the CGIAR Initiatives focusing on sustainable animal productivity. This Initiative aims to contribute to transforming livestock sectors in 7 target countries to make them more productive, resilient, equitable, and sustainable. Contributing to SAPLING’s overall objective, SAPLING - Vietnam country project, also known as Chăn-hênh, aims to contribute to transforming two livestock value chains (pigs and cattle) in the Northwest Highlands of Vietnam. This work is led by the International Livestock Research Institute (ILRI) and the Alliance of Bioversity and CIAT and is implemented in collaboration with various national partners from 2022-2024. SAPLING - Vietnam is implemented in two districts (Mai Son and Phu Yen) of one northern upland province (Son La). 9 out of 22 communes in Mai Son District and 12 out of 27 communes in Phu Yen District have been approved for SAPLING implementation. In the early stages, the work is primarily implemented in Mai Son District, specifically in four core communes (Chieng Luong, Chieng Chung, Hat Lot, Muong Bon), to test and validate innovation packages. Phu Yen District will be joined in the later stages for upscaling purpose drawing on lessons from Mai Son. A core component of SAPLING Vietnam’s overall strategy to strengthen the pig and cattle value chains is the formation or support to livestock farmers groups for both improved access of the farmers (women, men, youth and ethnic minorities) to input and output markets, as well as being a forum for capacity development and co-creation of solutions to issues regarding pig and cattle raising.